REVITALIZATION OF KUTTAB IN INDONESIA IN THE MODERN ERA AND ITS URGENCY IN FORMING CHILDREN'S LIFE SKILLS - Ulum, Fachrurizal Bachrul; Susanti, Linna; Nurhuda, Abid; Huda, Ali Anhar Syi’bul; Lathif, Nur Muhammad (Fitrah, 2024)
Currently, there are efforts to revitalize the function of kuttab in Indonesia through kuttab al Fatih. This research aims to analyze the kuttab al Fatih curriculum, especially in the field of life skills education as an Islamic educational institution. This research is a type of library research with descriptive and analytical methods. Data sources were taken through a literature review of books, articles, and literature relevant to the topic of discussion. The analysis technique uses Miles and Huberman's, which consists of data reduction, data display, and conclusion drawing. This research resulted in the conclusion that there is a uniqueness to the kuttab al Fatih curriculum which is summarized from the Qur'an and Hadith as well as the books of Salaf scholars. The association with the main reference of Islam can also be seen in learning students' life skills. The study in this research can add insight into the urgency of the kuttab concept as an Islamic educational institution in Indonesia. This research produces new discussions regarding the types of general and specific skills taught in the learning process at kuttab al Fatih.